HBO'S GAME OF THRONES : SEASONS 3 AND 4 - Taylor, C.A.; Benioff, David; Weiss, D.B. (London : Gollancz, 2014)
HBO's Game of thrones is one of the most remarkable success stories of recent television. Critically acclaimed, a ratings smash and going from strength to strength, the series will define fantasy for years to come. This second official companion book gives fans new ways to enter the world of Westeros and discover more about the beloved (and reviled) characters and the electrifying plotlines. Hundreds of set photos, production and costume designs, storyboards and insider stories reveal how the show's creators translate George R. R. Martin's best-selling fantasy series for the screen. Featuring interviews with key actors and crew members that capture the best scripted and unscripted moments from seasons three and four this special volume offers behind-the-scenes access to this ground-breaking and hugely successful series.
Keywords: Game of thrones (Television program)